HUBUNGAN KOMUNIKASI PEMASARAN DENGAN PRODUKTIVITAS USAHA TANAMAN HIAS DI KECEMATAN KADIA KOTA KENDARI - Widya Astuti; Ima Astuty Wunawarsih; Megafirmawanti Lasinta (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2026)
The development of the agricultural sector, particularly the ornamental plant subsector, has been identified as a significant economic opportunity. However, in the context of a competitive market, the success and productivity of businesses, particularly those operating on a micro, small, and medium scale, are influenced by a multitude of factors beyond mere technical production. The efficacy of marketing communication emerges as a pivotal element, as it has the potential to enhance business competitiveness and performance. The objective of this study is to examine the correlation between marketing communication and the productivity of ornamental plant businesses in Kadia District, Kendari City. The present study employs a quantitative approach, utilizing a descriptive-correlational research design. The research population consists of all ornamental plant traders operating in the promotion and sales locations of Kadia District agricultural products, totaling eight individuals. The census method was employed as the sampling technique, while data collection techniques included interviews, surveys, and documentation. The study's focal point was the examination of the relationship between marketing communication and ornamental plant business productivity. The data analysis in this study was conducted quantitatively. The results indicated that the marketing communications of ornamental plant traders in Kadia District, Kendari City, were classified as "good," while their business productivity was categorized as "very good." A subsequent Spearman's rank correlation analysis revealed a positive and significant relationship between marketing communication and business productivity, with a correlation coefficient of 0.586 (p < 0.05). This coefficient is classified as moderate. The optimization of direct marketing, interactive marketing, and promotional activities contributes to improving the efficiency, effectiveness, and quality of the business. The enhancement of marketing communication strategies constitutes a pivotal element in the augmentation of productivity and competitiveness among ornamental plant enterprises, accomplished in a sustainable manner.